Penyuluhan Fisioterapi pada Komunitas Lansia tentang Osteoarthritis Lutut di Posyandu Cantewa, Mojolangu, Kota Malang - Fadillah, Arvin; Sri Sunaringsih Ika Wardojo; Eleonora Elsa Sucahyo (Rena Cipta Mandiri, 2025)
Aging is a process of increasing age that involves a decline in the body's ability to repair itself, leading to psychological problems, physical, mental, and socioeconomic decline. Older adults often experience joint problems that interfere with their activities and independence. Knee osteoarthritis (OA) is one of the main causes of knee pain in the elderly, characterized by degeneration of joint cartilage, stiffness, and limited movement. This condition has an impact on the decline in quality of life and independence of the elderly. The prevalence of joint disease in Indonesia is quite high, especially in people over the age of 55. OA is more common in women due to hormonal, anatomical, and physical activity factors. This activity aims to provide physiotherapy education on prevention, non-pharmacological treatment, and simple exercises to support knee function in elderly people with OA. The educational activity was carried out at the Cantewa Health Center, Mojolangu, Malang City, with 15 participants (1 male, 14 females). The methods used included interactive lectures, discussions, and demonstrations of quadriceps strengthening exercises and knee muscle stretching. The results of the activity showed an increase in participants' understanding of risk factors, symptoms, and simple exercises in the prevention and management of knee OA. This activity has implications for increasing the awareness of the elderly to perform light physical exercises regularly as a strategy to maintain knee joint health. Community-based physiotherapy education is expected to be carried out continuously.